Pengaruh disiplin kerja dan kepuasan kerja terhadap kinerja karyawan - Novalita Silalahi; Wilson Bangun (Universitas Kristen Maranatha, 2020)
One of the key factors for an organization's success lies in its human resources or employees. Optimal employee performance supports the organization achieving its goals. In this study, problems were found in employee performance, which was the result of a student satisfaction survey on employee services at Maranatha Christian University that had not reached 100%. The purpose of this study was to determine the effect of work discipline and job satisfaction on employee performance. The University staffs consisting of 131 Permanent Administration Workers and 58 Permanent Household Workers are the objects of this study. The research method used was descriptive and explanatory. The results showed that there was a significant influence of work discipline on employee performance. Job satisfaction variable was also found that there was a significant effect on employee performance. Work discipline and job satisfaction are important factors in improving employee performance.